An Update on the Key Factors Required for Plant Golgi Structure Maintenance - Rui, Qingchen; Tan, Xiaoyun; Liu, Feng; Bao, Yiqun (Frontiers in Plant Science, 2022)
Plant Golgi apparatus serves as the central station of the secretory pathway and is the site where protein modification and cell wall matrix polysaccharides synthesis occur. The polarized and stacked cisternal structure is a prerequisite for Golgi function. Our understanding of Golgi structure maintenance and trafficking are largely obtained from mammals and yeast, yet, plant Golgi has many different aspects. In this review, we summarize the key players in Golgi maintenance demonstrated by genetic studies in plants, which function in ER-Golgi, intra-Golgi and post-Golgi transport pathways. Among these, we emphasize on players in intra-Golgi trafficking.